Public Preferences for Targeted and Universal Preschool - Erica H. Greenberg (SAGE Publishing, 2018)
For the past half century, debate over income-targeted and universal approaches to American preschool policy has divided advocates, policymakers, and practitioners. This is the first paper to inform the debate with evidence from public opinion. It begins with the design and fielding of a nationally representative poll of preferences for targeted and universal preschool (N = 1,000). This poll yields rich data with which to assess the causes and correlates of support for each approach. Results indicate that preschool preferences are conditioned by financial self-interest and egalitarian values and that a savvy policymaker should not necessarily endorse universal over targeted preschool. In fact, Americans facing the possibility of tax increases to fund public preschool and those who prioritize equality of opportunity prefer a targeted approach.